Delivery of plasmid encoding interleukin-12 gene into hepatocytes by conjugated polyethylenimine-based nanoparticles. (4th July 2017) - Khalvati, Bahman; Sheikhsaran, Fatemeh; Sharifzadeh, Sedigheh; Kalantari, Tahereh; Behzad Behbahani, Abbas; Jamshidzadeh, Akram; Dehshahri, Ali
Abstract: In the present investigation, polyethylenimine (PEI) was conjugated with succinic anhydride at four substitution degrees and the efficiency of the modified PEI derivatives in transferring the plasmid encoding interleukin-12 gene was evaluated. The results revealed that the conjugated PEI derivatives enhanced the transfection efficiency by up to 3-fold relative to unmodified PEI, with the highest increase occurring at conjugation degrees around 30%. The results demonstrated the ability of the modified PEI derivatives in condensation of the plasmid into the nanoparticles in the size range of approximately 100 nm. Also, the PEI derivatives exhibited substantial decrease in cell-induced toxicity.